Peranan Strategis Pembelajaran Aktif dalam Peningkatan Kualitas Pembelajaran di MAN 1 Jember: The Strategic Role of Active Learning in Enhancing the Quality of Education at Madrasah Aliyah Negeri 1 Jember - Moh. Sahlan (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2009)
The advancement of science and technology demands improved human resource quality through education, yet madrasah learning processes still face challenges such as low student activeness and achievement of learning objectives. This study aims to describe active learning strategies applied, supporting and inhibiting factors, responses of teachers and students, and the role of active learning strategies in enhancing learning quality at MAN Jember 1. Data were collected through interviews, observation, and questionnaires, then analyzed using Miles and Huberman's descriptive qualitative model. The findings show that strategies such as discussion, everyone is teacher here, snowballing, and jigsaw learning are frequently used with modifications. Supporting factors include facilities, teacher creativity, and student motivation, while inhibiting factors include class sizes over 40 and less conducive classroom conditions. Positive responses are seen in increased student enthusiasm and creativity, while negative responses occur when teachers lack mastery of strategies. In conclusion, implementing active learning strategies significantly improves learning activities and achievement of learning objectives. It is recommended that teachers master strategy procedures and that the madrasah head enhance supervision and coordination. Perkembangan ilmu pengetahuan dan teknologi menuntut peningkatan kualitas sumber daya manusia melalui pendidikan, namun proses pembelajaran di madrasah masih menghadapi tantangan seperti rendahnya keaktifan siswa dan pencapaian tujuan belajar. Penelitian ini bertujuan menjelaskan strategi pembelajaran aktif yang diterapkan, faktor pendukung dan penghambat, respons guru dan siswa, serta peranannya dalam meningkatkan kualitas pembelajaran di MAN Jember 1. Data dikumpulkan melalui wawancara, observasi, dan angket, lalu dianalisis secara deskriptif kualitatif model Miles & Huberman. Hasil penelitian menunjukkan bahwa strategi seperti diskusi, everyone is teacher here, snowballing, dan jigsaw learning sering digunakan dengan modifikasi. Faktor pendukung meliputi sarana prasarana, kreativitas guru, dan motivasi siswa, sementara penghambatnya antara lain jumlah siswa lebih dari 40 dan kelas kurang kondusif. Respon positif terlihat pada peningkatan semangat dan kreativitas siswa, namun respons negatif muncul jika strategi tidak dikuasai guru. Kesimpulannya, penerapan strategi pembelajaran aktif berperan signifikan dalam meningkatkan aktivitas dan pencapaian tujuan pembelajaran. Direkomendasikan agar guru menguasai prosedur strategi dan kepala madrasah meningkatkan pengawasan serta koordinasi.